(9+z)(3z-7)=0

Simple and best practice solution for (9+z)(3z-7)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (9+z)(3z-7)=0 equation:


Simplifying
(9 + z)(3z + -7) = 0

Reorder the terms:
(9 + z)(-7 + 3z) = 0

Multiply (9 + z) * (-7 + 3z)
(9(-7 + 3z) + z(-7 + 3z)) = 0
((-7 * 9 + 3z * 9) + z(-7 + 3z)) = 0
((-63 + 27z) + z(-7 + 3z)) = 0
(-63 + 27z + (-7 * z + 3z * z)) = 0
(-63 + 27z + (-7z + 3z2)) = 0

Combine like terms: 27z + -7z = 20z
(-63 + 20z + 3z2) = 0

Solving
-63 + 20z + 3z2 = 0

Solving for variable 'z'.

Factor a trinomial.
(-9 + -1z)(7 + -3z) = 0

Subproblem 1

Set the factor '(-9 + -1z)' equal to zero and attempt to solve: Simplifying -9 + -1z = 0 Solving -9 + -1z = 0 Move all terms containing z to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -1z = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -1z = 0 + 9 -1z = 0 + 9 Combine like terms: 0 + 9 = 9 -1z = 9 Divide each side by '-1'. z = -9 Simplifying z = -9

Subproblem 2

Set the factor '(7 + -3z)' equal to zero and attempt to solve: Simplifying 7 + -3z = 0 Solving 7 + -3z = 0 Move all terms containing z to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -3z = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -3z = 0 + -7 -3z = 0 + -7 Combine like terms: 0 + -7 = -7 -3z = -7 Divide each side by '-3'. z = 2.333333333 Simplifying z = 2.333333333

Solution

z = {-9, 2.333333333}

See similar equations:

| =7x+8-6x | | 9+2(x-13)=45 | | 7x-34=5x | | 12b=32 | | 4x^4+4x^3-24x^2=0 | | 0.11111111111111=-4 | | 6w-7=2z | | 129-2y=5(2y-3) | | 45=4y+17 | | t-10t-7t-(-4t)+(-6t)=18 | | 3-(1/2)r=5-(2/3)r | | 5(x+4)-2(x-3)=35 | | 2(2/5x)=8/15 | | BC=x+5 | | 2x^3+12x^2+5x=0 | | 9x-14=6x+28 | | 3x+k=c | | 5=3(3x-4)+2(3x+1) | | a^2b-3ab-10b=0 | | x^2-ax+(a+3)=0 | | 5x+9+3x-5=36 | | -3-2y=-13 | | -7=8x+13 | | x^3-2x^2-25x=0 | | -6x+7-3x=-2 | | 3xX+5=20 | | 4p-2p=20 | | 4(2x-13)+3x=58 | | 5(w-5)-7w=-27 | | 3(4u-2)=-30 | | 3x+18=2x-2 | | f^2-19=-1 |

Equations solver categories